Consumption of Sweet, Salty and Fatty Foods with Incidence of Obesity in Adolescents - Hanita Hanita; Muhammad Nur Hasan Syah (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Adolescent obesity is emerging as a global public health concern, primarily driven by unbalanced dietary habits and a lack of physical activity. This study aimed to explore the relationship between the consumption of sugary, salty, and fatty foods and the incidence of obesity among adolescents. A cross-sectional study was conducted involving 122 subjekts selected through simple random sampling. Data were analyzed using the chi-square statistical test. The findings revealed a significant association between the consumption of sugary foods (p <0.001) and fatty foods (p <0.001) with adolescent obesity, while no significant link was found between salty food consumption and obesity (p = 0.160). These results highlight the need for early prevention strategies through regulating the intake of sugary and fatty foods, promoting balanced nutrition, and encouraging an active lifestyle to reduce future obesity risks.